2021
DOI: 10.1186/s12889-021-11926-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring condom use decision-making among adolescents: the synergistic role of affective and rational processes

Abstract: Background Condom use remains the most effective behavioural method for the prevention of HIV and unplanned pregnancies. However, condom use remains inconsistent among young people. Exploring the condom use decision-making processes that adolescents engage in might provide information that would assist in the prevention of many challenges related to poor sexual and reproductive health outcomes. This study therefore aimed to explore the factors that influenced decision-making about sexual debut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Adolescent girls who did not want to use hormonal contraceptives opted to use condoms, particularly male condoms. Comparable findings have been reported in other studies [ 27 , 31 , 32 , 33 ]. Condoms are viewed as both a means of protection against diseases and prevention of pregnancy [ 33 ], although most use them for disease protection rather than the dual role that condoms provide (disease prevention and prevention of pregnancy) [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Adolescent girls who did not want to use hormonal contraceptives opted to use condoms, particularly male condoms. Comparable findings have been reported in other studies [ 27 , 31 , 32 , 33 ]. Condoms are viewed as both a means of protection against diseases and prevention of pregnancy [ 33 ], although most use them for disease protection rather than the dual role that condoms provide (disease prevention and prevention of pregnancy) [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…In line with the quality, scholarly work by Gambir et al [ 32 ] on the opportunities and challenges for the introduction of female condoms among young people in Zambia revealed that very few participants acknowledge female condoms due to misconceptions about their safety, how correct would they use them, availability, affordability of the condoms to them, and the limited power they had over the decisions on sexual activities. Nevertheless, the descriptive qualitative findings observed by Davids et al [ 33 ] on condom use decision-making among adolescents in South Africa depicted that male condoms were more promoted and distributed than female condoms, which again may be linked to the low use of female condoms and that sexual masculinity over sexual intercourses still prevails among young people.…”
Section: Discussionmentioning
confidence: 96%
“…While this is important, it is also beneficial to recognise that knowledge is not enough to trigger behaviour change. Therefore, beyond knowledge, it is important to understand whether and how emotions, intuitions and experiences shape BBVs/STIs risk and protective practices during the COVID-19 pandemic, as we still do not fully understand how these affective states shape health behaviours [21].…”
Section: Introductionmentioning
confidence: 99%